Lignin Based Embedded and Surface Deposited Nanoscale Zero Valent Iron for Cd(II) Remediation - Arachchi, Uthsara Malaweera; Hettige, Ayesha L; Alahakoon, Yasmitha A; Peiris, Chathuri; Mlsna, Todd; Gunatilake, Sameera (Faculty of Computing and Technology, University of Kelaniya Sri Lanka., 2023)
Vast industrialization occurring throughout the world has led to a drastic increase in water pollution by heavy metals. Cd is a heavy metal that has garnered significant concern due to its toxicity and adverse health effects on humans and other living organisms. Recent studies have focused on the application of Biochar (BC) supported carbothermally produced Nanoscale Zero Valent Iron (nZVI) for the remediation of a variety of contaminants. However, only limited research has been carried out to assess and compare the mechanisms of Cd removal and remediation efficiency by different types of carbothermally prepared nZVI. To address this issue, the present study investigated the application of two nanocomposites, Lig-eG@nZVI and Lig-sG@nZVI, produced through two carbothermal reduction routes at 1000 °C. In Lig-eG@nZVI, nZVI was embedded in the Lignin Biochar (Lig-BC) matrix while in Lig-sG@nZVI, nZVI was deposited on the Lig-BC surface. In this study, enhanced uptake of Cd(II) was observed with increasing pH with maximum uptake at pH 6. Cd sorption at 30 °C was evaluated using the Langmuir, Freundlich, Temkin, Redlich-Peterson, Sips, Toth and Jossens adsorption isotherm models. The experimental data was best fitted to Sips isotherm model, with a maximum Sips capacity of 9.688, 8.102 and 6.665 mg g-1 at 30 °C and pH 6 for Lig-eG@nZVI, Lig-sG@nZVI and Lig-BC, respectively. The two composites showed enhanced remediation due to the synergistic effect of remedial mechanisms of both nZVI and Lig-BC components. Possible adsorption mechanisms for BC include cation-π interactions, electrostatic attractions and surface complexation precipitation with minerals. Owing to the nearly identical standard redox potential of Cd with zero valent iron, the feasibility of Cd(II) remediation through reduction is very low and the only viable removal mechanism is sorption or surface complex formation. Fast remediation kinetics were observed for the three materials. According to thermodynamic studies conducted, the overall adsorption processes of all three materials were confirmed to be physisorptive, endothermic and spontaneous in nature. This study bridges the existing knowledge gap by conducting a comprehensive evaluation on the application of Lig-eG@nZVI, Lig-sG@nZVI and Lig-BC for the remediation of Cd(II) in aqueous media.
Keywords: Nanoscale zero valent iron, Biochar, Lignin, Cadmium remediation